رثاء الأبناء في شعر ابن نباتة المصري (ت 768هـ) مقاربة أسلوبيّة - Al-Dukhi | الدوخي, Muhammad bin Ibrahim | مـحمد بن إبراهيم (2023)
One of the most prominent poets who lost their sons in the Mamluk era is Jamal al-Din Ibn Nabatah. The days afflicted him with the loss of many of his sons, nearly sixteen. What no other has experienced in his children of constant loss and growing grief. The research is concerned with a study, the most prominent of which is what is contained in Ibn Nabathah’s lament for his sons from the stylistic point of view, and it came in three axes: 1. Emotional function. 2. Lexicon. 3. The analogy between the speaker and the betrothed (between the elegy and the elegy). | إن من أبرز الشعراء الذين فقدوا أبنائهم في العصر المملوكي جمال الدين ابن نباتة، فقد فجعته الأيام بفقد عدد كثير من أبنائه قارب الستة عشر ابنا، و هذه مصيبة كبرى، و كارثة تتابعت فصولها على الشاعر، فيصبح قوله في هذا الأمر ذا بال، فقد جرب ما لم يجربه غيره في أبنائه من الفقد المستمر و الحزن المتزايد. و البحث معني بدراسة أبرزها ما يحويه رثاء ابن نباثة لأبنائه من الوجهة الأسلوبية و قد أتى في ثلاثة محاور هي: 1. الوظيفة الانفعالية. 2. المعجم. 3. التناظر بين المتكلم و المخطب (بين الراثي و المرثي).